Application of Debye–Huckel and Bronsted-Bjerrum theory to mass transfer rate in supported liquid membrane; effect of ionic strength on separation factor, an analysis through case studies. Issue 5 (2nd November 2022) - Swain, Basudev; Sarangi, Kadambini; Park, Jay Ryang; Lee, Chan Gi
ABSTRACT: The Debye–Huckel and Bronsted-Bjerrum theory has been applied to supported liquid membrane process to understand the effect of ionic strength on separation factor. The effect of ionic strength due to different salts and their concentration on the separation factor of Cu(II) and Zn(II) by supported liquid membrane using Di-2 ethyl-hexyl phosphoric acid (D2EHPA) as a mobile carrier has been studied. For those studies, different salts, i.e., NaCl, NaNO3, NaClO3, Na2 SO4, and CH3 COONa, have been used. A mathematical model for the dependency of separation factor of Cu(II) and Zn(II) on ionic strength considering Debye–Huckel theory and Bronsted–Bjerrum theory has been developed. Experiments were carried out using a batch-type permeator of micro-porous polypropylene thin sheet as the solid support for the liquid membrane in the presence of different ionic strength of anions. The calculated separation factor is well agreed with the obtained results within 95% confidence interval.